Feed type regulates the fatty acid profiles of golden pompano Trachinotus ovatus (Linnaeus 1758). Issue 1 (1st January 2018) - Sun, Xiaoxiao; Guo, Huayang; Zhu, Kecheng; Zhang, Nan; Yu, Wenbo; Wu, Na; Jiang, Shigui; Zhang, Dianchang
ABSTRACT: The aim of the present study was to evaluate the effect of different feed types on the fatty acid profiles of golden pompano ( Trachinotus ovatus ). Three feed types (pelleted feed, frozen squid and frozen fish) were assigned to triplicate groups of fish (146.22 ± 3.26 g) in a total of 9 floating cages (50 fish per cage). Analysis of the fatty acid profiles of the three feed types revealed that frozen squid had the highest levels of long-chain polyunsaturated fatty acids (LC-PUFA), while the pelleted feed and frozen fish had lower levels of LC-PUFA, in particular eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). After three months of being fed a specific feed type, the fatty acid profiles of golden pompano muscle tissues were analysed. The highest levels of LC-PUFA were detected in fish fed with frozen squid. Golden pompano fed with frozen fish had intermediate levels of LC-PUFA content. The results suggest that the fatty acid composition of prey items can significantly affect the muscle fatty acid composition of the consumer. Muscle fatty acid composition could also be used as an indicator of diet type for golden pompano in the aquaculture industry.